Greening the workforce: a systematic literature review of determinants in green HRM - Irenius Dwinanto Bimo; Endang Sulistyaningsih (Cogent Business & Management)
This research sought to identify the factors that affect the adoption of Green Human Resource Management (Green HRM) within organizations, examining the subject from a theoretical and practical standpoint. The research used a systematic literature review methodology, employing the PRISMA guidelines to retrieve 26 articles that fulfilled the criteria. The findings indicate that contemporary Green HRM research concentrates on eight determinants. Nonetheless, the study identifies consistencies in the data; some evidence points to the significance of these determinants in promoting an organization’s Green HRM practices and overall sustainability, while at least one study suggests the relationship between specific determinants and Green HRM practices is not significant. However, there needs to be more focus on the context of Green HRM and the practicality of industrial relations within the organization and industries. This research aims to serve as a foundation for future investigations into this subject area, particularly as it relates to the decision-making process, which includes the existing industrial relations and prioritizing Sustainable Development Goals (SDG) in the strategic greening of human resources. Hence, there is an urgent demand for more Green HRM with sustainable practices, enhanced corporate governance, inclusive employee engagement approaches, and industrial relations.